PENGARUH ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP PURCHASE INTENTION MELALUI CUSTOMER TRUST SEBAGAI VARIABEL INTERVENING PADA PENGGUNA TIKTOK SHOP DI KOTA SEMARANG - Oliviera, Adib Maulana Decca; Hendar, Hendar (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstrak: Studi ini bertujuan menilai pengaruh Online Customer Review dan Online Customer Rating terhadap Purchase Intention dengan Customer Trust sebagai variabel intervening pada pengguna TikTok Shop di Kota Semarang. Ulasan dan rating pelanggan dianggap berperan penting dalam mengurangi ketidakpastian serta membentuk kepercayaan bagi penjual di platform e-commerce. Pendekatan yang digunakan adalah kuantitatif dengan metode Explanatory Research. Data dikumpulkan dari 120 responden pengguna TikTok Shop dan dianalisis menggunakan teknik Partial Least Square (PLS). Temuan studi menyatakan bahwa Online Customer Review dan Online Customer Rating memiliki pengaruh positif dan signifikan bagi Customer Trust dan Purchase Intention. Selain itu, Customer Trust berperan sebagai mediator dalam hubungan antara ulasan, rating, dan niat beli. Kesimpulannya, ulasan serta rating pelanggan berkontribusi penting dalam membangun kepercayaan dan mendorong minat beli konsumen di TikTok Shop. Kata Kunci: Online Customer Review; Online Customer Rating; Customer Trust; Purchase Intention; TikTok Shop. Abstract: This study aims to analyze the influence of Online Customer Reviews and Online Customer Ratings on Purchase Intention, with Customer Trust as a intervening variable among TikTok Shop users in Semarang City. Customer reviews and ratings are essential factors in reducing uncertainty and building trust toward sellers in the e-commerce era. The research adopts a quantitative approach using the Explanatory Research method. Data were collected from 120 TikTok Shop users in Semarang and analyzed using the Partial Least Square (PLS) method. The results indicate that Online Customer Reviews and Online Customer Ratings have a positive and significant effect on Customer Trust and Purchase Intention. Furthermore, Customer Trust is proven to mediate the relationship between reviews, ratings, and purchase intention. These findings highlight that customer reviews and ratings play a vital role in establishing trust and enhancing consumers’ purchase intentions on the TikTok Shop platform. Keywords: Online Customer Review; Online Customer Rating; Customer Trust; Purchase Intention; TikTok Shop.